AN EMPIRICAL STUDY ON THE IMPACT POVERTY ELEVATION - PRAYAD SAH (International Journal of Multidisciplinary Research and Studies, 2020)
These programmes, as they are carried out in India, are built on the foundation of women's self-help groups that are quite small (10–15 members) (SHGs). Training in literacy and other life skills, as well as access to low-cost credit, are all available to members of these organisations. Additionally, participants may learn about new options to generate revenue. SHGs are federated in these programmes into village organisations (VOs), which are then further federated into cluster-level federations (CLFs). The purpose of each of these federations is to provide a structure for linkages to financial services and government entitlement programmes, as well as to facilitate collective action and political participation among the poor. The Government of Bihar started the Bihar Rural Livelihoods Project in 2006, which is an example of one of these types of projects. This initiative was a part of the National Rural Livelihoods Mission (NRLM) of India, which was initiated in 2011 by the Ministry of Rural Development of India, which is India's national ministry in charge of rural development.